Representation of Jews and Anti-Jewish Bias in 19th Century French Public Discourse: Distant and Close Reading - Levis Sullam, Simon; Minello, Giorgia; Tripodi, Rocco; Warglien, Massimo (Frontiers in Big Data, 2022)
We explore through the lens of distant reading the evolution of discourse on Jews in France during the XIX century. We analyze a large textual corpus including heterogeneous sources – literary works, periodicals, songs, essays, historical narratives – to trace how Jews are associated to different semantic domains, and how such associations shift over time. Our analysis deals with three key aspects of such changes: the overall transformation of embedding spaces, the trajectories of word associations, and the comparative projection of different religious groups over different, historically relevant semantic dimensions or streams of discourse. This allows to trace moments of major semantic change, the evolution of stereotypes, and the dynamics of bias over a long time span during which dramatic institutional, political, economic and cultural changes unfolded. We suggest that the analysis of large textual corpora can be fruitfully used in a dialogue with more traditional close reading approaches – by pointing to opportunities of in-depth analyses that mobilize more qualitative approaches and a detailed inspection of the sources that distant reading inevitably tends to aggregate. We offer a short example of such a dialogue between different approaches in our discussion of the Second Empire transformations, where we mobilize the historian’s tools to start disentangling the complex interactions between changes in French society, the nature of sources, and representations of Jews. While our example is limited in scope, we foresee large potential payoffs in the cooperative interaction between distant and close reading.